Beyond Absolutes: Convergences and Divergences between Buddhist Philosophy and Postmodern Critique - Adhikari, Biswo Raj (The Outlook: Journal of English Studies, 2026)
The history of philosophy has been largely shaped by search for fixed grounds for knowledge, truth,  meaning and reality. However, this quest for fixity has been challenged by different philosophers and scholars in different periods of human history. Buddhist philosophy, particularly the Madhyamaka tradition, challenged the notions of permanent self, intrinsic essence, and independent existence through the doctrines of no-self, dependent origination, and emptiness. Likewise, postmodern critics such as Lyotard, Derrida, and Foucault questioned universal truths, stable meanings, and autonomous subjectivity by exposing the contingent, relational, and historically constructed nature of knowledge and identity. This article examines the major points of convergence and divergence between these two philosophies  originated from greatly varied historical and cultural contexts. It employs a cross-cultural comparative methodology to analyze the shared features and disparities between them. Drawing upon primary Buddhist texts, including Nagarjuna’s the Madhyamaka school and early Buddhist discourses, as well as the writings of Derrida, Foucault, and Lyotard, it makes a textual and conceptual analysis supported by relevant secondary scholarship. The analysis reveals that though both traditions question foundational assumptions, Buddhist thought locates critique in the context of transformation or liberation, whereas  postmodern critique remains as an open-ended and ongoing process of questioning. Buddhist critique intends to discover the path of liberation from suffering  through wisdom, compassion and self- discipline. Postmodern critique, on the other hand, centers on the critical investigation of discourse, knowledge and power structures, without pursuing an ultimate emancipatory objective.